The Validation of Amara (Authorized Conjectural Proof) of Vehicle ID Card to Prove Vehicle Ownership (Legal and Jurisprudential Analysis about the Contradiction between Authorized Persuasive Evidences and Certain Evidences in Vehicle Ownership - Sayyed Ahmad Mirkhalili; Ardavan Arzhang; Nasrollah Jafari; Majid Ghasemian Mazar (آموزه‌‌های فقه مدني)
The ownership of a vehicle can be proved by different proofs. The contradiction between these proofs is possible and probable. The contradiction between formal or conventional instrument and authorized conjectural proofs (ammarat) or with each other are types of these contradictions. In the contradiction between documents and authorized conjectural proofs (ownership amara) in the supposition of the simultaneousness, with the Corroborative evidences such as the document proof and negative evidences such as the inconsistency between the opposite supposition with the maxims, the document takes priority over amara. In the supposition of the different times some prefer amara because of its absolute validity. The preference of the document in this supposition is supported by the proofs of the previous mentioned supposition. The debate and argument about the evidences of the vehicle green card it is resulted that the part (the part which proves the owner of the vehicle plate) which police legally and exclusively have the authorization to establish it has been believed that the formal document and the other part (the part shows the vehicle ownership) it is not believed the formal instrument. But pursuant to the Islamic prevalent maxim -as the basis for the validation of ammarat- and because the ammarat are not restricted to the mentioned and known ones it is thought that green card is amara. It is a strong and logical amara which owes its power and effectiveness to the most cases and the behavior of most contract parties and it indicates the transfer of the vehicle ownership. Of course like other evidences and amara, the way to prove the opposing side is not blocked.